1988
DOI: 10.1007/bf02372651
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation de la toxicité deBacillus thuringiensis surSpodoptera frugiperda

Abstract: Cinquante deux souches de B. thuringiensis appartenant ~ 13 s6rovars ont 6t6 test6es sur des chenilles n~onates de Spodoptera frugiperda en contaminant la surface du milieu semi-synth6tique d'~levage. Deux souches du s6rovar kenyae et une autre du s~rovar tolworthi provoquent ie plus de mortalitY, suivies par les souches des s~rovars aizawai et kurstaki. Les souches les moins actives appartiennent aux s~rotypes alesti, dendrolimus, sotto et colmeri. L'action des souches sur le d6veloppement larvaire a aussi 6t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Polanczyk et al (1999) evaluated in vivo activities of Bt strains on S. frugiperda, and observed that suspensions of Bt aizawai HD 68 and Bt thuringiensis 4412, containing 3x 10 8 cells/ ml, induced effective mortality. Similar results were obtained by Hernandez (1988). Ramanujam et al (2020) with field trials observed efficacy of three sprays of M. anisopliae ICAR-NBAIR Ma-35 and B. bassiana ICAR-NBAIR Bb-45.…”
Section: Resultssupporting
confidence: 85%
“…Polanczyk et al (1999) evaluated in vivo activities of Bt strains on S. frugiperda, and observed that suspensions of Bt aizawai HD 68 and Bt thuringiensis 4412, containing 3x 10 8 cells/ ml, induced effective mortality. Similar results were obtained by Hernandez (1988). Ramanujam et al (2020) with field trials observed efficacy of three sprays of M. anisopliae ICAR-NBAIR Ma-35 and B. bassiana ICAR-NBAIR Bb-45.…”
Section: Resultssupporting
confidence: 85%
“…The results obtained in this study appeared that transcojugant Tr 4 is higher pathogenic causing 100% toxicity index than other bioinsecticides used in this study .The same trend was obtained by Hernadez ( 1988 ) on subspecies Bt aizawai , B. thuringiensis and Bt Kurstaki, who observing mortality of 80% , 100 % and 70 % respectively , using 3 x10 7 cells / ml . The virulence assays showed that transconjugant Tr 4 was the most active recombinant isolate with an LC 50 of 1.93x10 5 ppm followed by Tr 6 , Tr 7 Tr 1 and Tr 5 with an LC 50 of 2x 10 5 , 2x10 5 , 2.3 x10 5 , 2.3 x10 5 ppm d c a b a b…”
Section: Conjugation and Hydrolysis Of Colloidal Chitinsupporting
confidence: 82%
“…Some time ago, the efficacy of this microorganism against S. frugiperda was considered questionable, but more recently the increment in researches on the use of Bt against this lepidopterous brought some interesting results (4,10). The objective of this work was to report the selection of Bt strains with potential to control the fall armyworm.…”
Section: Introductionmentioning
confidence: 99%